THE USE OF THE SPIRITUAL VALUES OF THE COUNTRY IN EXTRACURRICULAR EDUCATIONAL ACTIVITIES - D.A. Bobomurodov; T.N. Kori (Scholar Express Journals, 2023)
In the article, there is a word about the study of the spirituality and history of the country, taking into account the interests, aspirations and abilities of the parents, based on the principles of independence, mutual respect and cooperation in choosing extracurricular activities and club activities at school, volunteering, independence in choosing the type of activity, and the wide use of them in the education of young people. held.
Keywords: contests; sports competitions; performances; talks